RELIABILITAS PENILAIAN ASPEK PSIKOMOTORIK MENGUNAKAN TES FORMATIF DAN SUMATIF PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR NEGERI PANDAN PAMEKASAN - Sa'i, Mad; Hunain, Ishaq; Maghfiroh, Muliatul (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2024)
Reliability is the level or stability of the results of the results of two measurements of the same thing. The expected measurement results will be the same if the measurements are repeated at different times. The reliability or maintainability of a score is very important in determining whether the test has presented a good measurement or not. This study aims to determine the reliability of the assessment evaluation implemented in Pandan Elementary School in the form of formative and summative assessments. This study uses quantitative methods with data collection techniques, reduction analysis, and drawing conclusions. The source of data in this study uses primary data obtained from interviews with Islamic Religious Education and Ethics teachers through a scientific approach. The respondents of this study consisted of the teacher council and the fifth grades students of the State Elementary School 1 Pandan Pamekasan. The reliability results from a the measurement of psychomotor aspects at the Pandan Pamekasan State Elementary School showed (0.008065201579854) with very low reliability.